Imperialistinen trippi Kaukoitään: Coppolan Ilmestyskirja. Nyt Vietnamin sodan historiatulkintana - Kimmo Ahonen; Rami Mähkä (Finland, 2022)
An Imperialistic trip to the Far East: Francis Ford Coppola’s Apocalypse Now as a historical interpretation of the Vietnam War
American-produced films have shaped images of the Vietnam War and acted as a means of handling the national past. In this article, we examine Francis Coppola’s film Apocalypse Now (1979) as an interpretation of the Vietnam War. We focus on the historical contextualization of the film: how it resonates with the history of the Vietnam War and is a part of the history of Hollywood’s treatment of the subject. We also examine Apocalypse Now’s relationship with imperialism and its nature as a war spectacle.
The production of Apocalypse Now was complicated and took more than a decade to be completed. This article uses both the original theatrical release (1979) and the extended “Redux” version from 2001 as its source material. Of the latter, we focus especially on the “French Plantation” scene, which was omitted completely from the original version. The scene clearly attempts to contextualize the Vietnam War and for that reason is an important source for analyzing Apocalypse Now as an interpretation of the historical event.
Finally, we examine the film as a historical film and, as such, a part of history culture. The film, and the “French Plantation” scene in particular, carries politically-charged themes of decolonization, imperialism and US history. Our argument is that Apocalypse Now, which featured several controversial events and phenomena experienced by people participating in the film’s production, both reflected and actively “wrote” the history of the Vietnam War.